Retrieval of Gallbladder Through Epigastric Vs Umbilical Port After Laparoscopic Cholecystectomy - Awan, Muhammad Younus; -Al-Hassan, Rabea; Akram, Maqsood (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the effectiveness of epigastrics vs. umbilical port after laparoscopic cholecystectomy by measuring the time taken to retrieve the gall bladder, post-operative pain, and infection.Study Design: Comparative prospective study.Place and Duration of Study: Department of Surgery Combined Military Hospital Abbottabad, from Jan to Jun 2019.Methodology: A total of 106 patients underwent laparoscopic cholecystectomy. Patients were randomly divided into two groups. Inclusion criteria were patients with symptomatic gallstones. Exclusion criteria were patients with comorbid medical conditions, acute cholecystitis, Empyema gall bladder, bile or stone spillage, and BMI >40. Time taken to retrieve the gall bladder, pain, and wound infection were used to compare the effectiveness of port sites. The results were collected on proforma and analyzed by using SPSS version 23.Results: Total 106 patients, having mean age of 45.90 ± 14.49 years. Gender distribution was similar (p=0.314). Retrieval time of gall bladder in epigastric group was 9.2 ± 2.98 and in umbilical group 9.73 ± 3.57 this difference was insignificant (p=0.516). In epigastric group pain was perceived in 3.69 ± 1.77 and in umbilical group 3.28 ± 1.39 with p-value of 0.062 which was nonsignificant. Wound infection in epigastric group was 1.07 ± 0.266 and in umbilical group 1.05 ± 0.233 with p-value of 0.439 which was in significant.Conclusion: Both port sites are equally effective and depend on Surgeon’s preference.